Community structure of mites (Arachnida: Acari) in six rubber tree clones - Daud, Rodrigo Damasco [UNESP]; Fazzio Feres, Reinaldo Jose [UNESP] (Taylor & Francis Inc, 2013)
Host plant cultivar may determine the occurrence and abundance of both herbivorous arthropods and of other species that interact with them. We analysed the acarofauna in six rubber tree clones to identify the effect of plant cultivar on community organization of these arthropods. We analysed 10 plants of clones GT 1, PB 217, PB 235, PB 260, PR 255, and RRIM 600 every 14 days, on average, for one year. We recorded 352,426 mites from 43 species and 16 families. Phytophagous mites were the most abundant functional group, followed by mycophagous and predaceous mites. However, mite community structure varied between clones. Mite abundance peaked in clone PB 235, while it had the lowest level in PB 260. The highest estimated richness was found in clones GT 1 and PB 235. Clones PB 235, PR 255, and RRIM 600 were the most similar in mite species composition. Plant cultivars affected the abundance of phytophagous species, which in turn influenced the occurrence of competing species (i.e., less abundant phytophagous species) and predatory mites. Our results indicate that rubber tree cultivar strongly influences mite community organization.
Keywords: acarofauna; bottom-up effect; plant cultivar; Hevea brasiliensis; herbivory resistance; species richness